Pengembangan Sistem Monitoring Kandang Ayam dengan Penerapan Komputasi Pervasif - Ali Ali; Agung Setia Budi; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
One of the factors that affect quality of broiler chicken is its coop environment condition. Farmers need to maintain optimum coop environment by maintaining temperature at 20-25Â°C, humidity in the range of 50-70%, and ammonia concentration at 0-5ppm. These problems can be overcome by system that monitors coop environment, so farmers can take the necessary action to maintaining it. The size of the cage, which is quite large, is a blockage for system implementation. Based on these reasons, implementation of WSN can meet the requirements while increasing the flexibility of the system. But, WSN system has some deficiency, such as complicated and time-consuming configurations. Therefore, implementation of pervasive computation into the system going to reduce human intervention and time used for system configuration. Chosen pervasive computation is a sensor node that can identify other nodes and connecting each other to system network. ESP8266 is used to process the data and deliver it using wireless. Output of the system is a website. From the test result, node capability to identify other nodes with average of 56.67% at four locations. While to connect with WiFi network at a distance level 3 to 4 meter, 8 to 10 meter, and 15 to 18 meters, node time to connect averaging at 48.8575 second. At same distance level, service discovery found the system with successful rate average at 73.33%